2005
DOI: 10.1039/b403203a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nanostructures from peptide–synthetic hybrid block copolymers: Complex, stimuli-responsive rod–coil architectures

Abstract: The synthesis, solution and solid state self-assembly properties of a series of polyisoprene-b-poly(epsilon-benzyloxycarbonyl-L-lysine) PI-b-PZLys and polyisoprene-b-poly(L-lysine) PI-b-PLys block copolymers have been examined. The formation of stimuli-responsive micelles in water has been studied as a function of pH and ionic strength using static and dynamic light scattering, UV-circular dichroism and transmission electron microscopy. The observed change in the micelles dimensions has been directly attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 40 publications
11
106
1
Order By: Relevance
“…Similarly, Lecomandoux and coworkers reported spherical micelles from poly(isoprene) 49 -b-PLys 123 which showed a size change from 23 nm to 44 nm from pH 11 to 6 in a saline solution. 65 Interestingly, they also reported a similar system of poly(butadiene) 48 -b-poly (LGA) 114 (PB-b-PLGA), that resulted in spherical micelle formation that only showed a size change of ca. 8 nm through the helix-coil transition; they mention that this smaller size change could be a result of folding or disruption of the PLGA helices.…”
Section: Assembly and Responsiveness Of Peptide-based Diblock Copolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Lecomandoux and coworkers reported spherical micelles from poly(isoprene) 49 -b-PLys 123 which showed a size change from 23 nm to 44 nm from pH 11 to 6 in a saline solution. 65 Interestingly, they also reported a similar system of poly(butadiene) 48 -b-poly (LGA) 114 (PB-b-PLGA), that resulted in spherical micelle formation that only showed a size change of ca. 8 nm through the helix-coil transition; they mention that this smaller size change could be a result of folding or disruption of the PLGA helices.…”
Section: Assembly and Responsiveness Of Peptide-based Diblock Copolymersmentioning
confidence: 99%
“…Liu and coworkers also reported schizophrenic assembly behavior of a dual responsive diblock copolymer, poly(N-isopropyl acrylamide) 65 -b-poly(LGA) 110 (PNIPAM 65 -b-PLGA 110 ). 76 At pH below 4 and at 25 C, they report spherical micelles formation with PNIPAM as the corona and the hydrophobic PLGA as the core.…”
Section: Assembly and Responsiveness Of Peptide-based Diblock Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…pendently studied a number of synthetic polymer-polypeptide block copolymers with varying hydrophobic blocks as well as varying the amino acids in the polypeptide blocks [11,17,[20][21][22][23][24][25][26]. These studies resulted in a number of pH-responsive micelles and vesicles whereby the responsiveness is due in part to the helix-coil secondary structure transition within the peptide chain.…”
Section: Introductionmentioning
confidence: 99%
“…Babin et al observed that the a-helix to b-sheet transition temperature for PZLys blocks in polyisoprene-b-PZLys block copolymers increases with increasing the degree of polymerization (DP) of PZLys blocks. [18] The transition temperature for a PZLys block with a DP n of 75 is % 155 8C, [18] which is close to the temperature (160 8C) at which we annealed our PFS-bPZLys block copolymer samples. Therefore, our study was focused on block copolymer PFS-b-PZLys 2, in which the DP n of PZLys block is 180, corresponding to a transition temperature higher than 200 8C.…”
Section: Resultsmentioning
confidence: 89%